2003
DOI: 10.1038/sj.bjc.6601068
|View full text |Cite
|
Sign up to set email alerts
|

ICBP90 belongs to a new family of proteins with an expression that is deregulated in cancer cells

Abstract: ICBP90 (Inverted CCAAT box Binding Protein of 90 kDa) is a recently identified nuclear protein that binds to one of the inverted CCAAT boxes of the topoisomerase IIa (TopoIIa) gene promoter. Here, we show that ICBP90 shares structural homology with several other proteins, including Np95, the human and mouse NIRF, suggesting the emergence of a new family of nuclear proteins. Towards elucidating the functions of this family, we analysed the expression of ICBP90 in various cancer or noncancer cell lines and in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
147
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(162 citation statements)
references
References 27 publications
(36 reference statements)
8
147
0
1
Order By: Relevance
“…Although UHRF1 promoter bears a CpG island, no DNA methylation was found in normal or tumor tissue, excluding the possibility of an epigenetic expression feedback loop. As UHRF1 is a known E2F1 target, 29,45 we also examined E2F1 mRNA expression levels in this sample set. Indeed, a strong relationship was observed between the expression levels of the 2 genes, supporting the concept that UHRF1 regulation is under the control of the pRb/E2F1pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although UHRF1 promoter bears a CpG island, no DNA methylation was found in normal or tumor tissue, excluding the possibility of an epigenetic expression feedback loop. As UHRF1 is a known E2F1 target, 29,45 we also examined E2F1 mRNA expression levels in this sample set. Indeed, a strong relationship was observed between the expression levels of the 2 genes, supporting the concept that UHRF1 regulation is under the control of the pRb/E2F1pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of this hypermethylation and its maintenance are not clearly understood but they likely target the expression of specific genes involved in the DNA damage response. We hypothesized that UHRF1 (Ubiquitin-like, containing PHD and RING Finger domains, 1) could be a major effector of the p73 deregulation, since this nuclear protein is known to be over-expressed in numerous cancer cell lines and tissues [8][9][10][11]. 4 Several studies have shown that UHRF1 participates in the control of cell proliferation and cell cycle transition from G1 to S, by regulating the expression of several genes, including RB1 and p16 INK4A [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…There are several lines of evidence that UHRF1 deregulation may impair the control of G1/S transition during cell cycle checkpoint activation [8,9,14]. Since such activation is known to occur during the DNA damage-related apoptosis of TQ [23][24][25][26], we analyzed the expression levels of UHRF1 and its partners DNMT1 and HDAC1 in TQ-treated Jurkat cells.…”
mentioning
confidence: 99%
“…The tumour suppressor p53, which is deficient in 50% of all human cancers (Hussain and Harris, 2000), indirectly downregulates UHRF1 through the upregulation of p21/WAF1 and subsequent deactivation of E2F1 (Arima et al, 2004). Expression of UHRF1 is upregulated in various cancers, including breast, prostate, lung, astrocytomas, pancreatic cancers, and cervical cancer (Mousli et al, 2003;Unoki et al, 2004;Crnogorac-Jurcevic et al, 2005;Jenkins et al, 2005;Lorenzato et al, 2005;Oba-Shinjo et al, 2005). Overexpression of UHRF1 in these cancers may be partially due to the inactivation of p53, although there are most probably several pathways which regulate UHRF1.…”
mentioning
confidence: 99%
“…The UHRF1 recruits DNA methyltransferase 1 (DNMT1) to the site with proliferating cell nuclear antigen (PCNA) and methylates the newly synthesised strands (Sharif et al, 2007;Achour et al, 2008). The UHRF1 promotes G1/S transition (Arima et al, 2004;Jeanblanc et al, 2005) and is a direct target of E2F transcription factor 1 (E2F1) (Mousli et al, 2003;Unoki et al, 2004;Abbady et al, 2005). The tumour suppressor p53, which is deficient in 50% of all human cancers (Hussain and Harris, 2000), indirectly downregulates UHRF1 through the upregulation of p21/WAF1 and subsequent deactivation of E2F1 (Arima et al, 2004).…”
mentioning
confidence: 99%